2019
DOI: 10.1634/theoncologist.2018-0807
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Patients with Ovarian Cancer

Abstract: Objective Polypharmacy has been associated with morbidity and mortality in patients with cancer. Data about polypharmacy among patients with ovarian cancer are limited. The primary objective of this study was to evaluate polypharmacy in a cohort of patients with ovarian cancer and to assess the evolution of polypharmacy from initial presentation to 2 years posttreatment. A secondary objective was to evaluate differences in polypharmacy between a subset of patients primarily treated in our comprehensive cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…It is the leading cause of gynecologic cancer-related deaths among women, causing 152,000 deaths yearly (Torre et al, 2018). Due to the missing early symptoms and the absence of effective early detection strategies, approximately 70% of OC patients were diagnosis at advanced stage presenting with metastases (Oldak et al, 2019). Although the treatment for OC has been greatly improved in recent decades, the recurrence is frequent and the 5-year overall survival rate remains poor (Coleman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is the leading cause of gynecologic cancer-related deaths among women, causing 152,000 deaths yearly (Torre et al, 2018). Due to the missing early symptoms and the absence of effective early detection strategies, approximately 70% of OC patients were diagnosis at advanced stage presenting with metastases (Oldak et al, 2019). Although the treatment for OC has been greatly improved in recent decades, the recurrence is frequent and the 5-year overall survival rate remains poor (Coleman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have included only a small numbers of advanced lung cancer patients and have shown relatively high prevalence (7%-80%) of PP among the patients and its negative impact on clinical outcomes [11,16,[34][35][36][37]. However, the heterogeneity of patients' disease states, baseline characteristics, or treatment modalities across target populations or cancer types might impair the applicability of these results to different clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to determine whether older advanced NSCLC patients take more medications compared to other cancer patients. Simple comparisons with previous studies might be inappropriate because of different medication thresholds or time slots (simultaneous [16,17] or continuous [4,41]) used to measure PP. The most commonly used threshold of PP is >=5 concomitant medications, so medications among older advanced cancer patients might indicate the potential utility of other thresholds (excessive polypharmacy [17], major polypharmacy [12]) to detect high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypharmacy, defined as using a large number of medications, is often a consequence of treatment for multiple comorbidities and is not specific to PCT. 7 Among adults, persons battling cancer, 8 the elderly, 9 and veterans 10 are the most-reported populations for whom polypharmacy occurs and needs to be addressed. Tinetti et al highlighted that unintended polypharmacy can result from compliance across multiple, noncoordinated clinical practice guidelines (CPGs) for patients with multiple conditions.…”
Section: Introductionmentioning
confidence: 99%